LEARNING MEDIA USING MONOSNAP AT SMK NEGERI 1 SUKASADA DURING COVID-19 PANDEMIC - Sukmadewi, Made Ika; Putra, I Nyoman Adi Jaya; Myartawan, Putu Ngurah Wage (Language and Education Journal Undiksha, 2022)
The goal of this research is to develop learning media in the form of video by using screencast application named Monosnap to assist students learned English during COVID-19 outbreak while increasing their vocabulary skill. In the process of developing the learning media, the researcher applied Design and Development (D&D) method proposed by Richey and Klein (2007). Interview guide, questionnaire, and expert judgment were instruments used to collect the data in this research. The subject of this research was students of SMK Negeri 1 Sukasada in Buleleng regency, North Bali. The result indicated that the learning media made by Monosnap was relevant to the eleven criteria of a good learning media in the form of video. Not only that, but it was also categorized as a good media. The learning media in the form of video was a necessary media to be used to assist students learned during COVID-19 outbreak while increasing students’ vocabulary skill.